The impact of androgen actions in neurons on metabolic health and disease. (15th April 2018) - Morford, Jamie J.; Wu, Sheng; Mauvais-Jarvis, Franck
Abstract: The male hormone testosterone exerts different effects on glucose and energy homeostasis in males and females. Testosterone deficiency predisposes males to visceral obesity, insulin resistance and type 2 diabetes. However, testosterone excess predisposes females to similar metabolic dysfunction. Here, we review the effects of testosterone actions in the central nervous system on metabolic function in males and females. In particular, we highlight changes within the hypothalamus that control glucose and energy homeostasis. We distinguish the organizational effects of testosterone in the programming of neural circuitry during development from the activational effects of testosterone during adulthood. Finally, we explore potential sites where androgen might be acting to impact metabolism within the central nervous system. Highlights: The androgen receptor is expressed in regions of the hypothalamus that control metabolic homeostasis in males and females. Androgen deficiency predisposes male rodents to T2D and obesity via loss of peripheral and hypothalamic AR actions. Developmental androgen excess predisposes females to metabolic dysfunction via action in the hypothalamus and periphery. Adult androgen excess predisposes female mice to obesity via impairment of central leptin signaling and BAT thermogenesis.